Refrigeration, air conditioning and heat pumps / G. F. Hundy, A. R. Trott, T. C. Welch - Hundy, G F
This book provides a comprehensive introduction to the principles and practice of refrigeration. Clear and comprehensive, it is suitable for both trainee and professional HVAC engineers, with a straightforward approach that also helps inexperienced readers gain a comprehensive introduction to the fundamentals of the technology. With its concise style and broad scope, the book covers most of the equipment and applications professionals will encounter. The simplicity of the descriptions helps users understand, specify, commission, use, and maintain these systems.